The Concept of Informativeness of Scientifc Knowledge in K. Popper’s Philosophy - Plėšnys, Albinas (Problemos, 1984)
The problem of informativenes of scientific knowledge, a major problem in philosophy, is raised and considered in K. Popper’s works. The evolution of K. Popper’s views on the above problem are revealed in the article. The correlation of K. Popper’s views to those of R. Carnap is discussed and the estimation of the solutions suggested by K. Popper are presented.